2019
DOI: 10.3390/rs11060713
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Urban Objects in Cloud Shadows on the basis of Fusion of Airborne LiDAR and Hyperspectral Data

Abstract: Feature extraction in cloud shadows is a difficult problem in the field of optical remote sensing. The key to solving this problem is to improve the accuracy of classification algorithms by fusing multi-source remotely sensed data. Hyperspectral data have rich spectral information but highly suffer from cloud shadows, whereas light detection and ranging (LiDAR) data can be acquired from beneath clouds to provide accurate height information. In this study, fused airborne LiDAR and hyperspectral data were used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…It can be concluded that the classification method can obtain excellent results for both random forest classifier and the object-based classifier. Man et al (2019) extracted urban objects in shadow areas with hyperspectral and LiDAR data, and demonstrated the advantage of LiDAR data in improving the classification accuracy of urban objects in shadow areas, including trees and buildings [70]. The study has also shown that the combined use of airborne LiDAR and hyperspectral data could improve the classification accuracy of trees in shadow areas.…”
Section: Performance Of Different Classification Methods For Trees and Grasses Extractionmentioning
confidence: 99%
“…It can be concluded that the classification method can obtain excellent results for both random forest classifier and the object-based classifier. Man et al (2019) extracted urban objects in shadow areas with hyperspectral and LiDAR data, and demonstrated the advantage of LiDAR data in improving the classification accuracy of urban objects in shadow areas, including trees and buildings [70]. The study has also shown that the combined use of airborne LiDAR and hyperspectral data could improve the classification accuracy of trees in shadow areas.…”
Section: Performance Of Different Classification Methods For Trees and Grasses Extractionmentioning
confidence: 99%
“…According to the difference of micro-Doppler effects [45] of rotating parts due to the difference in structure and rotating speed, features of the amplitude deviation coefficient, time domain waveform entropy and frequency domain waveform entropy are extracted to classify targets. Finally, features extracted from multi-wave gates sparse echo data are weighted and fused to train and test the support vector machine (SVM) [46][47][48] model for classification. Experimental results show that the proposed algorithm can improve the classification probability, and four wave gates echo data in weighted features fusion used to extract features is the optimal wave gate number for target classification.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the echo received by the two receivers was used for fusion detection to improve the detection performance of the target. The dual platform cooperative detection system constructed in this paper has the advantages of a bistatic radar system and single radar system [25][26][27]. The detection range was extended and the detection performance improved, which lays a foundation for future research of the airborne radar cooperative detection system.…”
Section: Introductionmentioning
confidence: 99%